La Matriz de Capacidades y Desempeños (MCD) y el Algoritmo del Desarrollo Humano (ADH) - Gonzales de Olarte, Efraín (Pontificia Universidad Católica del Perú. Fondo Editorial, 2010)
Given that human development is a complex process involving multiple components and determiningfactors, multidimensional indicators are needed. On the basis of the extensive literatureon the subject, we advance two new indicators: the Matrix of Capabilities and Functioning (MCF), and the Algorithm of Human Development (HDA). The MCF is composed of vectors of capabilities and functionings, based on Sen’s idea of Refined Functionings. It is based in a matricial framework, both static and dynamic. The main purposeof constructing this index is to study how different sets of capabilities relate to alternative functionings, to produce diverse outcomes. The Human Development Algorithm (HAD) is a multidimensional index concerning the setof goods and services needed to complete a life cycle. The HDA is a socio-economic contextindicator. It is composed of the main «satisfactors» or basic goods and services needed: food, health, education, housing, social security, decent employment and retirement programs, thatmight be available to all throughout of life cycle. This indicator shows the material progress reached by each country or region as well the institutional organization, private and public, and the degree of social cohesion and solidarity.

Dado que el desarrollo humano es un proceso complejo que tiene múltiples componentes ydeterminantes, es necesario tener indicadores multidimensionales tales como la Matriz de Capacidadesy Desempeños (MCD) y el Algoritmo del Desarrollo Humano (ADH). El MCD está compuesto de vectores de capacidades y de desempeños, basado en la idea de Sen sobre desempeños refinados. Está basado en un marco conceptual matricial, tanto estático como dinámico. El propósito principal de la construcción del índice es estudiar cómo diferentes conjuntos de capacidades con desempeños pueden producir distintos resultados. El ADH es un índice multidimensional relacionado con el conjunto de bienes y servicios que senecesitan para completar un ciclo de vida. El ADH es un indicador de contexto socioeconómico. Está compuesto de los principales satisfactores o bienes y servicios básicos que se requieren: alimentos, salud, educación, vivienda, seguridad social, empleo decente y sistema de pensiones, quedeben estar disponibles durante todo el ciclo de vida. Este indicador muestra el progreso material alcanzado por cada país o región, tanto como la organización institucional pública y privada, y el grado de cohesión social.
Keywords: Desarrollo Humano; Desarrollo; Recolección de Datos y Metodología de Estimación; https://purl.org/pe-repo/ocde/ford#5.02.01